Transitioning to low carbon energy in Malaysia: examining renewable energy policy barriers using multi-stakeholders approach - Saiful Mulok, Shahzelan (2020)
This report presents the findings from a study regarding transitioning to low carbon energy in Malaysia using multi-stakeholder approach.Energy has been the key driver of social and economic development. With increasing population and developing economies in many countries around the world, energy consumption is an increasingly important force shaping global energy trends. However, the energy sector, which predominantly dependent on fossil fuels is the world biggest polluter.The Malaysian energy sector is still heavily dependent on non-renewable fuel such as fossil fuels, coals and natural gas as a source of energy contributing to 83.8% as at 2017.Given the importance to transition to low carbon energy alternatives, and the presence of multi-dimension factors that have led to the current slow-moving state of renewable energy in Malaysia, this study is aims to understand the barriers that cause the slow growth of RE development in Malaysia. Additionally, the study also aims to apply stakeholder theory to explore whether stakeholder’s interests and concerns are fully addressed and considered when designing policy actions.